Design and Comparative Characterization of Water Level IDE Sensors at Resonant Frequencies - Ranjan, Prem; Chowdhury, Atanu (Recent Advances in Electrical & Electronic Engineering, 2025)
BackgroundThis paper reports the design and characterization of three Interdigital electrode (IDE) water-level sensors at resonant frequencies. The geometries of the proposed IDE sensors are comb type, circular type, and Archimedean spiral type. These IDE sensors have been fabricated by the printed circuit board technology. The sensor’s performance has been evaluated on both tap and distilled water.MethodsThe multiple resonant frequencies are investigated for the frequency span of 40 Hz to 110 MHz using a 4294A impedance analyzer. The peak of the projected admittance graph appeared at the first resonant frequency. This first resonant frequency is chosen here for the characterization of the proposed sensors.ResultsThe study asses that the variations in resonant frequency are caused by both the sensor's geometry and the water under test. The resonant frequency subtly states that sensors can be presented as lumped element equivalent series RLC circuits. In this work, an attempt has been made to show that the change in capacitance plays a pivotal role in estimating the resonant frequency. It is found that the sensor’s sensitivity decreases with water elevation and always be negative.ConclusionThe circular and Archimedean spiral sensors have comparable sensitivity performance, while the comb IDE sensor is found to be the most sensitive. The IDE sensor features the highest sensitivity at 1 cm of water elevation. The circular and spiral IDE sensor more closely follows the reference resonant frequency   when compared with the comb IDE sensor.
Keywords: capacitance